Początki parafii Najświętszego Serca Pana Jezusa w Brześciu na Grajewskim Przedmieściu - Żurek, Waldemar Witold (Archiwa, Biblioteki i Muzea Kościelne, 2021)
The Polish city of Brest on the Bug (the Eastern borderlands), developing after World War I, needed another Roman Catholic Church for the local faithful. Granting the requests of the faithful, the bishop of Pińsk Zygmunt Łoziński canonically erected - on 2 January 1932- the Parish of the Sacred Heart of Jesus, which was the second parish in Brest, with the Parish of Elevation of the Holy Cross being the fi rst one. Rev. Józef Moniuszko was the first parish priest and its organizer. The bishop sent one vicar to help him in parish work. Soon some parish groups of the faithful were organized: the Third Order of St. Francis of Assisi, the Pontifi cal Society for the Propagation of the Faith, Brotherhood of the Guard of Honour of the Sacred Heart of Jesus, the Association of “ Mary’s Children”. All of those groups intensifi ed the religious life of the parish.